2014
DOI: 10.3390/nu6062206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on the Level of Circulating High-Sensitivity C-Reactive Protein: A Meta-Analysis of Randomized Controlled Trials

Abstract: Vitamin D might elicit protective effects against cardiovascular disease by decreasing the level of circulating high-sensitivity C-reactive protein (hs-CRP), an inflammatory marker. Thus, we conducted a meta-analysis of randomized controlled trials to evaluate the association of vitamin D supplementation with circulating hs-CRP level. A systematic literature search was conducted in September 2013 (updated in February 2014) via PubMed, Web of Science, and Cochrane library to identify eligible studies. Either a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 31 publications
4
101
2
4
Order By: Relevance
“…Recent studies have suggested the role of 25(OH) D in lowintensity chronic inflammation in healthy and T2DM subjects [30,31]. To our knowledge, there have been few RCTs in which inflammatory biomarkers, including hs-CRP, were secondary outcomes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested the role of 25(OH) D in lowintensity chronic inflammation in healthy and T2DM subjects [30,31]. To our knowledge, there have been few RCTs in which inflammatory biomarkers, including hs-CRP, were secondary outcomes [30].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been few RCTs in which inflammatory biomarkers, including hs-CRP, were secondary outcomes [30]. Our interventional study (the Tromsø vitamin D and T2DM trial) is the only RCT to date with a follow-up period as long as 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted his systematic review based on the international referred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines [13,14]. We registed our study in the International Prospective Register of Systematic Reviews, PROSPERO (registration no: CRD42016036932).…”
Section: Methodsmentioning
confidence: 99%
“…Therfore there is substantial uncertainty about the net effect of vitamin D supplementation on CRP levels. Asystematic study which has addressed this issue dates back to 2014 inlcuding only a few studies [13]. Therefore, a comprehensive evalaution of evidence is needed to achieve an evidence-based conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Для определения значимости назначения препаратов витамина D в изме-нении уровня циркулирующего СРБ был проведен ме-таанализ, в который были включены результаты иссле-дований, опубликованных до февраля 2014 г., и пред-ставленные в PubMed, Web of Science и Cochrane library (Chen N. et al, 2014). Для статистической обработки данных было отобрано 10 исследований, объединив-ших 924 участника.…”
unclassified